Schizandrin, an Antioxidant Lignan from Schisandra chinensis, Ameliorates Aβ1–42-Induced Memory Impairment in Mice. (22nd May 2012) - Hu, Di; Cao, Yunfeng; He, Rongrong; Han, Na; Liu, Zhihui; Miao, Lijing; Yin, Jun
Abstract : In the present study, we examined the effect of schisandrin (SCH) of Schisandra chinensis on the amyloid-beta1–42 - (A β 1–42 -) induced memory impairment in mice and elucidated the possible antioxidative mechanism. Mice were intracerebroventricular (i.c.v.) injected with the aggregated A β 1–42 and then treated with SCH (4, 12, and 36 mg/kg body weight) or donepezil (DPZ), a reference drug (0.65 mg/kg) by intragastric infusion for 14 days. Noncognitive disturbances and cognitive performance were evaluated by locomotor activity test, Y-maze test, and water maze test. Antioxidative enzyme activities including superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) and levels of malondialdehyde (MDA), glutathione (GSH), and oxidized glutathione (GSSG) within the cerebral cortex and hippocampus of mice were measured to elucidate the mechanism. Our results showed that SCH significantly improved A β 1–42 -induced short-term and spatial reference memory impairments in Y-maze test and water maze test. Furthermore, in the cerebral cortex and hippocampus of mice, SOD and GSH-px activities, GSH level, and GSH/GSSG ratio were increased, and levels of MDA and GSSG were decreased by the treatment of SCH. These results suggest that SCH is a potential cognitive enhancer against Alzheimer's disease through antioxidative action.